Lattice Boltzmann modelling of isothermal two-component evaporation in porous media. (25th January 2023) - Fei, Linlin; Qin, Feifei; Zhao, Jianlin; Derome, Dominique; Carmeliet, Jan
Abstract: Abstract : A mesoscopic lattice Boltzmann model is implemented for modelling isothermal two-component evaporation in porous media. The model is based on the pseudopotential multiphase model with two components to mimic the phase-change component (e.g. water and its vapour) and the non-condensible component (e.g. dry air), and the cascaded collision operator is used to enhance the numerical performance. The model is first analysed based on Chapman–Enskog expansion and then validated by the theoretical solution of an isothermal diffusive evaporation problem. We then discuss in detail the implementation of wettability based on a geometric function scheme and further validate the model with microfluidic evaporation experiments. We apply the method to simulate the convective evaporation of a dual-porosity medium and investigate the effects of inflow vapour concentration ( Y_vapour, in ) and contact angle ( θ ) on the evaporation. Simulation results reproduce the typical transition from the constant evaporation regime (CRP) at large liquid saturation ( S ) to the receding front period (RFP) at small S, with an intermediate falling rate period in between. The dependence of the average evaporation rates on Y_vapour, in and θ during CRP and RFP is investigated. A universal scaling formulation for the evaporation rate during CRP is found with respect to the concentration-related mass transfer number B_Y, contact angle θ and inflow Reynolds number Re, i.e. ER_CRP = k_3( 1 + B_Y ) · [ ( 1 + Re ) + k_2 ][ (θ ) + k_1 ], where k_1, k_2 and k_3 are fitting parameters.